Implementasi Dakwah Keluarga di Era Digital - Ridwan, Muhammad; Edwin Rewira, Andi (STAI Publisistik Thawalib Jakarta, 2022)
The family is the most important part in shaping the nation's future generation. No wonder someone who comes from a good family will generally be a good person. But behind it all there are other factors that affect the growth and development of family members such as schools, neighbors, and including the times. The digital era, where information and communication technology makes everything easy, effective and efficient. Both in the fields of business, education, culinary, tourism. However, behind the advantages of the digital era, there are negative impacts of individual traits experienced by family members, lack of social interaction, lack of attention and sympathy, and excessive consumerism by using applications. This is where the importance of the appearance of the role of the head of the family is not only normative to the extent of the father and mother, but must be able to appear as a da'wah interpreter who conveys the positive values of the teachings of the Prophet Muhammad. The importance of this role is different from having to know the appropriate material to be delivered as well as the method and method of delivery used.